CONSUMER PERCEPTION ON MARKETING MIX ASPECTS OF PACKAGED COOKING OIL PRODUCTS IN BESITANG DISTRICT, LANGKAT REGENCY - Nabilah Yusriati; Rita Ariani; Cut Rozana Sari (Jurnal Mahasiswa Agribisnis, 2026)
AbstractThis research was conducted in Besitang District, Langkat Regency, North Sumatra Province. Consumer perceptions of packaged cooking oil products are influenced by various marketing mix aspects, including price, product, promotion, and place. Differences in consumer characteristics and socio-economic conditions may lead to variations in consumer assessments of these marketing mix aspects. The study aims to determine consumer perceptions of the marketing mix aspects of packaged cooking oil products in Besitang District, Langkat Regency, North Sumatra. The analytical method employed is descriptive qualitative, using a Likert scale as a tool to measure the level of consumer perception, allowing respondents' attitudes and assessments to be classified into specific categories based on the scores obtained. The analysis was carried out by descriptively detailing respondents' answers to obtain an overview of consumer assessments across each aspect of the marketing mix: price, product, promotion, and place. The results indicated that consumer perception of the marketing mix for packaged cooking oil in Besitang District achieved an average index value of 74.11%, which falls into the "good" category. Viewed from each individual aspect, consumer perception of price (74.55%), product (76.11%), and promotion (72.93%) were in the good category, while perception of place (72.88%) was also categorized as good. Based on purchase percentages, 78.79% of respondents stated they regularly purchase packaged cooking oil, while 21.21% stated they do not purchase it regularly. Keywords: Consumer Perception, Likert Scale, Marketing Mix, Packaged Cooking Oil.